An Analysis of Mathematical Connection Ability in Cubes and Cuboids Learning Materials Based on Gender Differences - Hotipah, Putri; Pujiastuti, Heni (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study was aimed to describe the students' mathematical connection ability in cube and cuboid learning materials based on gender differences. The research method employed was descriptive-qualitative. This research involved 6 subjects consisted of 3 males and 3 females students. Based on the results and discussion, it can be concluded that the total average score of male students was 54.5% and female students were 63.3%. Based on the categories of ability, male students were in a low category, while female students were in the moderate category. Several factors might cause this to happen, one of which was the low basic mathematical knowledge.